In vivo evaluation of the angiogenic and antimicrobial properties of tualang honey using a fvll-tidckness burn wounds in animal model in comparison to hydro fibre - Teng, Khoo@Koo Yan (2010)
Tangential excision and skin grafting are inevitable in managing full-thickness bums. Wound bed preparations prior to surgery are necessary in order to prevent wound infection and promote wound healing. Honey can be used to treat bum wounds. However, not all the honey is the same. The objective of this study is to evaluate the effect on the wound contraction, antimicrobial properties and histopathological aspects of Tualang honey in full-thickness bum wounds in a rat model, in comparison to Aquacel dressings. Thirty-six female Sprague Dawley rats were randomly divided into three groups. Under anesthesia, three full-thickness bum wounds were created on the dorsum of the rats. The full-thickness bum wounds were inoculated with a specific organism (104 ), namely Pseudomonas aeruginosa (n=12), Klebsiella pneumoniae {n=l2), or Acinetobacter baumannii (n=l2). The three bum wounds were dressed with Tualang honey, plain Aquacel or Aquacel Ag. Swab samples were obtained every 3 days (day 3, 6, 9, 12, 15, 18 and 21) for microbiological analyses. Clinical assessments were performed. At day 7, 14 and 21 days of bum, tissue samples were sectioned and histopathological examination was performed. The result of this study reveals a rapid 32.26% reduction in wound size by day 6 (p = 0.008) in the Tualang honey-treated wounds, and 49.27% by day 15 (p = 0.005). The wounds remained smaller by day 18 (p < 0.032). Tualang honey-treated rats demonstrated a reduction in bacterial growth in Pseudomonas aeruginosa inoculated wounds (p = 0.005). However, Aquacel-Ag® and plain Aquacel-treated wounds are superior to honey-treated wounds with Acinetobacter baumannii (p = 0.035). Neutrophil count was reduced in honey-treated wound on day 7 in both Acinetobacter baumannii and Klebsiella pneumoniae-inoculated wounds (p < 0.05) and similar fmdings on day 14 in Pseudomonas aeruginosa-inoculated wounds (p = 0.003). Granulation thickness of honey treated wound was 50.42J.Lm compared to Aquacel-treated wound (24.87Jlffi) on day 14 in Pseudomonas aeruginosa group (p = 0.045). On day 21, in Klebsiella pneumoniae group, there was complete epidermis coverage of the wound (p = 0.002) and increased thickness of granulation tissue (p = 0.001) in honey treated group. In histologic analysis of new capillary fonnation, there was no statistical significance between all the dressings. In conclusion, this experiment shows the positive effect ofTualang honey as a topical dressing for full-thickness bum wounds in an animal model. Tualang honey has better results with regard to the eradication of Pseudomonas aeruginosa. It also promotes bum wound healing process on wound inoculated with Pseudomonas aeruginosa or Klebsiella pneumoniae.